Адаптивная система управления электротехническим комплексом - Жуков, Станислав Федорович; Важинский, Антон Иванович (НТУ "ХПИ", 2017)
Проведено исследование поведения промышленных объектов в условиях наличия транспортного запаздывания в канале обратной связи. Выполнено математическое моделирование, исследованы частотные характеристики системы управления электротехническим комплексом. Полученные теоретические результаты послужили основой для синтеза системы управления с идентификацией параметров объекта и возможностью адаптивной настройки параметров регуляторов.

To improve the management of industrial objects and to eliminate the time delay in measuring channel it is advisable to develop a model that takes into account the dynamics of the process. We have obtained mathematical model in tabular form or in the form of equations. As a result, we have found pulsed or transient characteristic of the object, as well as the corresponding spectral characteristics, which are used for structural and parametric identification. Selecting an optimal model based on the adequacy of regulatory criteria of quality and sustainability with minimum complexity of the model. We found an array of data, which characterized the parameters of the control object. This allowed us to determine the character of transition processes. New analytical dependences, which were obtained by mathematical modeling and simulation, confirmed in experimental studies, and became the basis for the synthesis of software. Analytical descriptions of process, which included in the predictive control model of electrical equipment, allowed us to minimize the effect of time delay in the measurement channel.
Adaptive control system of electrical equipment
Keywords: транспортное запаздывание; частотная характеристика; адаптация параметров; предиктор; identification; time delay